Gdańsk - Wrzeszcz ul. Grunwaldzka 40-44 / foto Karol Nowaliński. - Nowaliński, Karol (1935- ). (1980)
Przedstawia kamienice przy ul. Grunwaldzkiej 40-44, w kamienicy nr 44 mieściła się biblioteka, ok. 1985 r.